2018
DOI: 10.3390/jfmk3040053
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Upper and Lower Extremity Strength on Performance-Based Sarcopenia Assessment Tests

Abstract: The optimal management of sarcopenia requires appropriate endpoint measures to determine intervention efficacy. While hand grip strength is a predictor of morbidity and mortality, lower extremity strength may be better associated with functional activities in comparison to hand grip strength. The purpose of our study was to examine the comparative association of upper and lower extremity strength with common measures of physical performance in older adults. Thirty community-dwelling men, aged 62.5 ± 9.2 years,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
39
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(43 citation statements)
references
References 53 publications
2
39
0
2
Order By: Relevance
“…The EWGSOP2 definitions specify that muscle strength can be determined by the grip strength test or the five-repetition chair stand test, suggesting interchangeability of these measures [ 11 ]. However, previous research have shown poor associations between upper- and lower body strength [ 13 , 14 ], and we report differences in anthropometric parameters and physical function when using either the grip strength- or chair stand test to define probable sarcopenia. While usually preferred out of feasibility, studies show that grip strength testing may be insufficient in detecting associations between muscle strength, hospitalization and mortality [ 31 ].…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…The EWGSOP2 definitions specify that muscle strength can be determined by the grip strength test or the five-repetition chair stand test, suggesting interchangeability of these measures [ 11 ]. However, previous research have shown poor associations between upper- and lower body strength [ 13 , 14 ], and we report differences in anthropometric parameters and physical function when using either the grip strength- or chair stand test to define probable sarcopenia. While usually preferred out of feasibility, studies show that grip strength testing may be insufficient in detecting associations between muscle strength, hospitalization and mortality [ 31 ].…”
Section: Discussionmentioning
confidence: 54%
“…EWGSOP2 guidelines recommend grip strength or chair stand tests for determination of upper- or lower-body strength respectively, and have called for validation of their new operational criteria in different populations [ 11 ]. To ensure proper diagnosis of sarcopenia status, it is important to evaluate how the strength measures perform against each other, as previous research have reported weak associations between strength in upper- or lower-body extremities, in addition to different associations with physical function [ 13 , 14 ]. It is thus unclear whether grip strength and chair stand tests can be used interchangeably as primary defining measures, and how selecting one or the other may affect sarcopenia prevalence estimates.…”
Section: Introductionmentioning
confidence: 99%
“…The age groups of the participants may not represent the advanced sarcopenia in the relatively elderly Western population. The quadriceps muscles strength was not measured, which has a greater influence on the quality of life in sarcopenia than the HGS [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…The findings in the study population of 62–73 years may not represent other age groups. We did not measure the lower extremities’ strength, which is an important determinant of quality of life in aging [ 40 ].…”
Section: Discussionmentioning
confidence: 99%